Polysaccharide Capsules Equip the Human Symbiont Bacteroides thetaiotaomicron to Modulate Immune Responses to Dominant Antigen in the Intestine - Hsieh, Samantha (J Immunol, 2020)
Bacteria express multiple diverse capsular polysaccharides (CPSs) for protection against environmental and host factors, including the host immune system. Using a mouse TCR transgenic CD4+ T cell, BθOM, that is specific for Bacteroides thetaiotaomicron (B. theta) and a complete set of single CPS-expressing B. theta strains, we ask whether CPSs can modify the immune responses to specific bacterial antigens. Acapsular (Acap) B. theta, which lacks all B. theta CPSs, stimulated BθOM T cells more strongly than wild-type B. theta. Despite similar levels of BθOM antigen expression, many single CPS-expressing B. theta strains were anti-stimulatory and weakly activated BθOM T cells, but a few strains were pro-stimulatory and strongly activated BθOM T cells just as well or better than Acap. B. theta strains that expressed an anti-stimulatory CPS blocked antigen delivery to the immune system, which could be rescued by Fc receptor-dependent antibody opsonization. All single CPS-expressing B. theta strains stimulated the innate immune system to skew towards M1 macrophages and release inflammatory cytokines in a MyD88-dependent manner, with anti-stimulatory CPS activating the innate immune system more weakly than pro-stimulatory CPS. The expression of anti-stimulatory versus pro-stimulatory CPSs on B. theta outer membrane vesicles (OMVs) also regulated immune responses. Moreover, anti-stimulatory and pro-stimulatory single CPS-expressing B. theta strains regulated the activation of antigen-specific and polyclonal T cells as well as clearance of dominant antigen in vivo. These studies establish that the immune responses to specific bacterial antigens can be modulated by a diverse set of CPSs.